Gulf Cooperation Council Stock Returns and the Effect of Domestic Monetary Policy Shocks - Sbia, Rashid; Hamdi, Helmi; Tas, Bedri Kamil Onur; Rousane, Sahel Al (International Journal of Economics and Financial Issues, 2016)
The aim of this paper is to analyze the effect of monetary policy on stock returns and stock return variability in the Gulf Cooperation Council (GCC) Countries namely; Bahrain, Kuwait, Oman, Qatar and Saudi Arabia (United Arab Emirates was excluded for non-availability of the data). The empirical results reveal that the impact of policy interest rates on stock markets varies among GCC countries. These results have an important policy implication for the single market project and monetary union between GCC countries. Keywords: Stock Market, Monetary Policy, Gulf Cooperation Council Countries JEL Classifications: G17, G18, E43, E47